NEUROPROTECTIVE ROLE OF ASCORBIC ACID: ANTIOXIDANT AND NON-ANTIOXIDANT FUNCTIONS - Kumar, Arun; Saini, Reena V; Saini, Adesh K (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Ascorbic acid (AA) or Vitamin C is an important antioxidant which participates in numerous cellular functions. Although in human plasma its concentration is in micromolars but it reaches millimolar concentrations in most of the human tissues. The high ascorbate cellular concentrations are generated and maintained by a specific sodium-dependent Vitamin C transporter type 2 (SVCT2, member of Slc23 family). Metabolic processes recycle Vitamin C from its oxidized forms (ascorbate) inside the cells. AA concentration is highest in the neurons of the central nervous system (CNS) of mammals, and deletion of its transporter affects mice brain and overall survival. In the CNS, intracellular ascorbate serves several functions including antioxidant protection, peptide amidation, myelin formation, synaptic potentiation, and protection against glutamate toxicity. SVCT2 maintains neuronal ascorbate content in CNS which has relevance for neurodegenerative diseases such as Alzheimer's, Parkinson's, and Huntington's disease. As ascorbate supplements decrease infarct size in ischemia-reperfusion injury and protect neurons from oxidative damage, it is a vital dietary antioxidant. The aim of this review is to assess the role of the SVCT2 in regulating neuronal ascorbate homeostasis in CNS and the extent to which ascorbate affects brain function as an antioxidant.